Deep convolutional GAN-based data augmentation for medical image classification - Datta, Joy; Durdana, Bedria; Rafi, Salwa (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.